Dispatch of fuel cells as Transmission Integrated Grid Energy Resources to support renewables and reduce emissions. (15th June 2015) - Shaffer, Brendan; Tarroja, Brian; Samuelsen, Scott
Highlights: TIGER Stations are 10–100 MW scale clusters of fuel cells installed at substations. TIGER Stations enable electric grid support. TIGER Stations can provide significant carbon and NOx emission reductions. Flexibility of TIGER Stations is required at higher renewable penetrations. TIGER Stations have very low NOx emissions and support urban air quality goals. Abstract: The increasing demand on electric grids to support high penetrations of intermittent renewables, enhance power quality, increase reliability and resiliency, and provide ancillary services, is leading to local power generation on both sides of the meter. This paper describes the potential attributes of deploying 10–100 MW scale clusters of fuel cells installed at distribution substations to enable electric grid support through the provision of baseload and various levels of load following services. Such deployments, referred herein as Transmission Integrated Grid Energy Resource (TIGER) Stations, can also contribute to achieving air quality and climate goals through several high value attributes including high efficiency, ultra-low pollutant emissions, and near zero acoustic emissions. To quantitatively assess these benefits, a 5 GW deployment of TIGER Stations in the California electric system was analyzed using the Holistic Grid Resource Integration and Deployment (HiGRID) model at 33%, 43%, and 50% renewable penetration. The analysis establishes that (1) TIGER Stations have the potential to reduce carbon emissions and NOx emissions even when operated as baseload systems, and (2) TIGER Station load following capability is important for continued carbon emission reductions at higher renewable penetrations. Additional features of TIGER Stations, such as heat recovery or hybrid cycles, will further increase the attributes of TIGER Stations.